Chemical properties of Terminalia catappa wood - Richmond Acheampong; Kwaku Antwi; Mark Bright Donkoh; Michael Awotwe-Mensah; Frank Kofi Dorwu (Les)
Ghana’s forest is fast depleting as a result of over-dependency on the traditionally known timber species and high demand for wood products for structural works. This study seeks to determine the chemical properties and basic density of Terminalia catappa wood and its potential for structural application. Three mature trees of Terminalia catappa were acquired based on the diameter at the breast height (dbh) greater than 40 cm. In this study 160 samples of wood were used for the chemical properties and density tests. Chemical analyses were performed by using the TAPPI standards. The study revealed that there were higher cellulose and hemicellulose contents in the sapwood than in heartwood, and in the branchwood than in stemwood. Lignin and extractives content were higher in the heartwood than in sapwood, and in the stemwood than in branchwood. The basic density of the sapwood ranged from 473 to 649 kg/m³ and in the heartwood from 444 to 579 kg/m³ being the highest in the base portion and the lowest in the branches. The difference in wood density, which is greater in the base area than the branches, emphasizes how crucial it is to take wood quality into account for the best possible use across various tree portions. The study also clarifies the wood's suitability for structural and non-structural uses. These findings have the potential to influence sustainable forest management strategies and encourage the use of alternative timber to supplement the resource base.